ALIH KODE PADA MASYARAKAT TUTUR KELURAHAN RABANGODU UTARA, KECAMATAN RABA, KOTA BIMA, NTB - Indah Komalawati; Umi Hartati (Universitas Sarjanawiyata Tamansiswa, 2019)
This research aims to describe 1) the types of code-switching in the speech communities of North Rabangodu Village, Raba District, Bima City, NTB, 2) Function of code-switching during communicating is found in the speaking community of North Rabangodu Village, Raba District, Bima City, NTB, 3) The causes of the occurrence of code-switching in the speech community of North Rabangodu Village, Raba District, Bima City, NTB. The study included qualitative descriptive research. The data in this study are public utterances containing code-switching in a speech in the form of conversation. The data is obtained from data sources in the form of language usage in community speech carried out from January to February 2019 in of Â North Rabangodu Village, Raba District, Bima City, NTB. The method of providing data uses the refer method. The technique used is the recording and recordimg technique. The method of data analysis is a translational equivalent method and is pragmatically matched with the determinant element (PUP) technique. The method of presenting the results of the data analysis used is an informal method. The result of this study are as follows: 1) Types of code-switching in the speech communities of Noth Rabangodu Village, Raba District, Bima City, NTB, namely a) transfer internal code, b) transfer of external code, 2) The function of code switching during communication found in the speech community of North Rabangodu Village, Raba District, Bima City, NTB, a) connecting the conversation according to de language used last (triggering), b) mentioning the person intended in the conversation, 3) The causes of code-switching in the speech communities of North Rabangodu Village, Raba District, Bima City, NTB, a) speakers, b) partners, c) the presence of third speakers, d) subject matter, e) arousingÂ sense of humor